ACCIDENTAL CHILDHOOD NON-FOOD POISONINGS IN AMINU KANO TEACHING HOSPITAL KANO, NORTHERN NIGERIA - RO BELONWU; GD GWARZO; MB USMAN (Ntec Specialist, 2009)
Background: Childhood poisonings has been reported from several centers in Nigeria in the past 4 decades. Despite the periodic presentation of children with poisonings to the various health facilities in Kano state, there has been no reported study from Kano and adjoining catchment areas. Objectives: The objective of the study was to determine the pattern of non-food childhood poisonings and outcome. Method: The case notes of children admitted to the emergency paediatric unit (EPU) and paediatric medical ward (PMW) with history of accidental poisoning during a 7-year period (January 1999- December 2005) were reviewed. Relevant data extracted included the patient's age, sex, date of admission, poison ingested, clinical features and outcome. Results: During the 7-year period under review, there were 4900 paediatric admissions of which 74(1.6%) were cases of accidental poisoning. The commonest poisons were kerosene (74.3%), organophosphate insecticide (9.5%) and detergent (2.7%). Thirty-nine (52.7%) of the 74 cases of poisoning were in children below 2years of age. There were 43 males and 31 females, a male to female ratio of 1.4: 1. The mortality rate was 8.1%. Conclusion: The study has shown that accidental non food poisoning is a notable health problem in Kano and that kerosene was the most frequent cause of poisoning. The role of prevention of poisoning through government policies and health education is imperative.